Probe‐based confocal laser endomicroscopy for rapid on‐site evaluation of transbronchial biopsy specimens - Masao Takemura; Noriaki Kurimoto; Masahiro Hoshikawa; Toshitaka Maeno; Takeshi Hisada; Masahiko Kurabayashi; Takeo Inoue; Teruomi Miyazawa; Masamichi Mineshita (Thoracic Cancer, 2019)
Background Probe‐based confocal laser endomicroscopy (pCLE) is a novel, noninvasive technology that provides real‐time lung imaging during bronchoscopy. pCLE shows the elastic fiber network without the use of a fluorescent dye. Elastic fibers produce argon laser‐induced autofluorescence at a wavelength of 488 nm, but tumor cells do not produce autofluorescence at this wavelength. As a result, the tumor cells cannot be observed directly. Therefore, we stained transbronchial biopsy (TBB) specimens with acriflavine to evaluate the benign and malignant structures using pCLE of ex vivo samples and to determine whether rapid histopathological diagnosis of TBB specimens could be made via pCLE. Methods After bronchoscopy, 36 TBB specimens were stained with acriflavine and observed using pCLE. Benign and malignant lesions were classified by cell density and nuclear magnitude disparity. Results We defined the confocal laser endomicroscopic atypia classification from the findings of the cells. The sensitivity for malignancy was 91.3%, and the specificity was 76.9%. Both inter‐observer (κ = 0.48) and intra‐observer (κ = 0.57) agreement confirmed moderate agreement. Conclusion pCLE with acriflavine staining was useful to differentiate malignant from benign TBB specimens, and might be useful as a substitute for rapid on‐site evaluation of histopathological diagnosis.